Edutechnoentrepreneurship Training for Kindergarten Teachers and Parents in Creating a Technology-Based Creative Learning Environment - Sabariah Sabariah; Rufi'i Rufi'i; Adi Bandono; Suhari Suhari; Roberto Roberto; M. Lis Haryanto; Aas Setiani (STAI Publisistik Thawalib Jakarta, 2026)
The Edutechnoentrepreneurship training aims to enhance educators' and parents' digital proficiency in the innovative, interactive, and secure application of educational technology to facilitate early childhood learning. The Community Service Program commenced with a needs assessment, the creation of materials, and the formulation of practice-oriented activities. The activities took place in person at the Tambaksari Subdistrict Hall in Surabaya, utilizing Participatory Action Research (PAR) lectures, discussions, and question-and-answer sessions, facilitated by an LCD projector, a laptop, and an audio system. The training yielded substantial improvements in participants' comprehension and abilities. Educators and guardians utilized child-appropriate educational applications and created straightforward digital media, including instructional videos, interactive worksheets, and educational games, to enhance children's cognitive and linguistic development. Moreover, participants' understanding of digital safety improved, as evidenced by the adoption of parental control mechanisms and prudent screen time management. The training enhanced collaboration between schools and homes via communication on digital platforms. Participants' mindsets transitioned toward enhanced innovation, propelled by creative facilitators. Children exhibited heightened enthusiasm, confidence, and active engagement in the learning process. Despite challenges including limited devices and the necessity for continuous support, the program successfully cultivated an innovative, secure, and sustainable digital learning ecosystem.